Isolation of a high molecular weight actin-binding protein from baby hamster kidney (BHK-21) cells. - Schloss, J A (1979)
A high molecular weight protein (HMWP) with properties similar to those of both actin-binding protein (ABP) and filamin has been isolated from cultured baby hamster kidney (BHK-21) cells. The protein was present in an actomyosin-depleted sucrose extract of the cells and was eluted, upon gel chromatography on Sepharose 4B, near the void volume. The subunit migration on sodium dodecyl sulfate/polyacrylamide gels and the amino acid composition of HMWP were similar to those of ABP and filamin. HMWP bound to and crosslinked F-actin from rabbit muscle, as shown by the formation of a gel that was sedimented with low-speed centrifugation. This interaction was insensitive to temperature and low concentrations of calcium ions, although it may depend on the presence of myosin. Observation of thin sections of the actin-HMWP gel revealed crosslinked complexes of laterally aggregated actin filaments. The axial period of the dense crosslinks was 34 nm. The HMWP may be involved in regulation of microfilament organization.